Blue Growth and Green Decisions: Financing Sustainable Fisheries Entrepreneurship - Raghu, Mr. Tanna; Murthy , Dr. Kudumula Venkata Ramana; Mandala, Dr. Gangu Naidu (International Journal of Accounting and Economics Studies, 2025)
The article analyzes the fisheries entrepreneurship in Andhra Pradesh in terms of its investment planning and decision-making in the context of Sustainable Blue Economy finance. A structured questionnaire was administered to 120 entrepreneurs at small, mid- and large-scale business in the Visakhapatnam Port region, evaluating ten dimensions, such as environmental priority, knowledge of innovative finance instruments, and confidence in risk-management, on a five-point Likert scale. ANOVA with one way revealed that large-scale operators had significantly higher means on the prioritisation of the environment (F(2,117)=50.016, p<0.001), knowledge of Blue Economy finance tools (F(2,117)=70.241, p<0.001), and confidence in risk-management (F(2,117)=5.387, p=0.0058), whereas no size-related differences were observed in terms of access to capital, integration of valuation The results obtained point to serious gaps in knowledge and capability of smaller businesses and to the necessity of special capacity-building, simplified reporting systems and special concessional funding to make sustainable investment habits democratized in all sizes of fisheries entrepreneurship.